Integrating the Triple Bottom Line Framework for Wetland Management and Urban Livability: A Case of Upper Lake Bhopal, India - Borikar, Paurnima; Agrawal, Adarsh (Calibrating Urban Livability in the Global South, 2024)
Wetlands provide vital ecosystem services and biodiversity yet face threats from rapid urban expansion and population growth. The Bhoj Wetland of Upper Lake Bhopal, India, grapples with unplanned urban growth, encroachment, and pollution, jeopardizing its diverse ecosystem and community resilience. Employing the Triple Bottom Line framework, this study evaluates the interconnected sustainability of the Upper Lake wetland and urban livability across economic, social, and environmental dimensions. Analyzing secondary data and Geographic Information Systems, it examines wetland-livability linkages and the impacts of issues like invasive species, waste discharge, and unsustainable practices. Findings highlight sustainable wetland management's significance in maintaining ecosystem services, mitigating urbanization effects, and securing wetland benefits for present and future generations. The study emphasizes integrated conservation efforts, community involvement, and policy initiatives as critical for preserving urban wetlands. By underscoring the urgency of a triple bottom line approach balancing ecological integrity, societal well-being, and economic viability, this research provides a framework for sustainable urban planning and development, guiding cities globally in preserving wetland ecosystems for a resilient future.